2015
DOI: 10.1111/1467-8268.12119
|View full text |Cite
|
Sign up to set email alerts
|

Health Status and Labour Force Participation in Sub-Saharan Africa: A Dynamic Panel Data Analysis

Abstract: Sub-Saharan African countries face significant health challenges, with several countries still far from reaching the health-related targets of the Millennium Development Goals (MDGs). The implication of this on economic growth and individual welfare is daunting. An important channel through which population health affects economic performance is labour supply and productivity. The objective of the study was to investigate a macro level relationship between population health status and labour force participatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
25
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 20 publications
4
25
0
1
Order By: Relevance
“…Thus, the study concluded that all the 36 countries in Africa were heterogeneous; that is, POL model is insignificant to explain the impact of financial inclusion on longevity in Africa. This was consistent with the studies of Novignon et al (2015) that nations in Africa are not the same.…”
Section: Findings and Discussion Of Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…Thus, the study concluded that all the 36 countries in Africa were heterogeneous; that is, POL model is insignificant to explain the impact of financial inclusion on longevity in Africa. This was consistent with the studies of Novignon et al (2015) that nations in Africa are not the same.…”
Section: Findings and Discussion Of Resultssupporting
confidence: 92%
“…However, little is known about the extent to which financial inclusion affects health shocks in Africa, where formal health insurance is hardly accessible and limited. Observably, African countries lagged behind in the attainment of health-and welfare-related of recent past Millennium Development Goals (Novignon et al, 2015) perhaps because most Africans depend largely on out-of-pocket payments for medical-care services during their health shocks experiences. Health shocks, the unpredictable illnesses that reduce longevity and that quickly diminish health status of individuals (Leivea and Xub, 2008) is often sudden events.…”
Section: Introductionmentioning
confidence: 99%
“…Antiretroviral treatment of HIV1 patients in Kenya resulted in increased LFP (Thirumurthy et al, 2008), while HIV1 mine workers who later developed AIDS recorded a fivefold increase in absenteeism in Botswana (Habyarimana et al, 2008). Novignon et al (2015) found a positive and significant relationship between population health and LFP in the general and female populations in sub-Saharan Africa.…”
Section: Literature Reviewmentioning
confidence: 84%
“…Novignon et al . () found a positive and significant relationship between population health and LFP in the general and female populations in sub‐Saharan Africa.…”
Section: Introductionmentioning
confidence: 97%
“…Health capital determines individuals' labour productivity (Bridges & Lanson, 2011;Novignon et al, 2015;Straus & Thomas, 1995;Thomas & Straus, 1997) and labour participation (Lavy et al, 1995;Handa & Neitzert, 1999as cited in Bridges & Lanson, 2011. Poor health could reduce one's hours of labour supply or days worked (Pitt & Rosenweig, 1986;Ulimwengu, 2009), and one's health status has a significant impact on his/her participation in labour wages (Straus &Thomas, 1995;Mwabu, 2008;Novignon et al, 2015). Extended periods of illness are highly likely to have a negative impact on one's ability to supply labour and could affect the household's productivity (Ulimwengu, 2009).…”
Section: Human Capital: Health Labour and Productionmentioning
confidence: 99%